2008
DOI: 10.1007/s00414-008-0266-y
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the A189G mtDNA heteroplasmic mutation in relation to age in modern and ancient bones

Abstract: Abstract:The aim of this study was to demonstrate the presence of the A189G age-related point mutation on DNA extracted from bone. For this, a PNA/DNA sequencing method which can determine an age threshold for the appearance of the mutation was used.Initially, work was done in muscle tissue in order to evaluate the sensitivity of the technique and afterwards in bone samples from the same individuals. This method was also applied to ancient bones from 6 well preserved skeletal remains. The mutation was invariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Such "C-tracts" are prone to length heteroplasmy; in other words, one individual can have various mtDNA lengths in his or her cells which differ by the number of C's at these C-tracts [3,20]. Research on the cellular mechanisms and circumstances causing heteroplasmy is ongoing [8,12,14,16,19]. These C-heteroplasmies are not rare, but indeed are typical in the majority of casework.…”
Section: Introductionmentioning
confidence: 97%
“…Such "C-tracts" are prone to length heteroplasmy; in other words, one individual can have various mtDNA lengths in his or her cells which differ by the number of C's at these C-tracts [3,20]. Research on the cellular mechanisms and circumstances causing heteroplasmy is ongoing [8,12,14,16,19]. These C-heteroplasmies are not rare, but indeed are typical in the majority of casework.…”
Section: Introductionmentioning
confidence: 97%
“…In a previous study, we found that one of the most studied point mutations associated with age on muscle tissue (A189G) also accumulates in bone samples of aged individuals [16]. The aim of the present study was to show that the presence of another type of heteroplasmic mutation, the tandem duplications, is also linked with age in human bones.…”
Section: Introductionmentioning
confidence: 89%
“…They were collected during medico-legal autopsies from accidental death victims, secondarily identified. Among these, 29 double bone/muscle samples were extracted and screened for the detection of the A189G heteroplasmic mutation [16]. For the 53 remaining individuals, DNA was extracted from each sample (bone and muscle) with the PrepFiler™ Forensic DNA Extraction Kit (Applied Biosystems, AB, Foster City, CA) according to the manufacturer's instructions and then purified and concentrated with Microcon YM30 filters (Millipore, Billerica, MA, USA).…”
Section: Samples and Extractionmentioning
confidence: 99%
“…The fate of heteroplasmic mutations depends on several factors, including the replication rate of the cell, type and location of the variation (DiMauro and Davidzon, 2005;Lacan et al, 2008). Several mutant mtDNA varieties may be present at undetectable low concentrations, and the degree of heteroplasmy may also be tissue-specific.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%